Apical Function in Neocortical Pyramidal Cells: A Common Pathway by Which General Anesthetics Can Affect Mental State - Phillips, William A.; Bachmann, Talis; Storm, Johan F. (Frontiers in Neural Circuits, 2018)
It has been argued that general anesthetics suppress the level of consciousness, or the contents of consciousness, or both. The distinction between level and content is important because, in addition to clarifying the mechanisms of anesthesia, it may help clarify the neural bases of consciousness. We assess these arguments in the light of evidence that both the level and the content of consciousness depend upon the contribution of apical input to the information processing capabilities of neocortical pyramidal cells by selectively amplifying relevant signals. We summarize research suggesting that what neocortical pyramidal cells transmit information about can be distinguished from levels of arousal controlled by sub-cortical nuclei and from levels of prioritization specified by interactions within the thalamocortical system. Put simply, on the basis of the observations reviewed, we hypothesize that to be conscious is to have particular, directly experienced, percepts, thoughts, feelings, and intentions, and that general anesthetics affect consciousness by interfering with the intracellular processes by which particular activities are selectively amplified when relevant to the current context.